Selection of adhesive systems in treatment of tooth root caries (literature review) - I. G. Romanenko; N. I. Chepurova; A. S. Zueva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Adhesive dentistry is the foundation on the basis of which there have been global changes in the concept of adhesion of composite materials in therapeutic dentistry, protocols for fixing ceramic restorations in orthopedic dentistry. But a number of unsolved problems remained – the adhesion of composite materials to sclerosed dentin and tooth root cement, the sensitivity of the components of the adhesive systems to the wet environment of the oral cavity and spatial stability in the presence of dentinal fluid moving centrifugally in the dentinal tubules, the lack of restoration of periodontal attachment to the defect that occurs during tooth root caries. The review analyzes the results of studies on the use of self-etching adhesive systems in the treatment of root caries. The physician's ability to choose an adhesive system in a particular clinical case demonstrates his fundamental knowledge and minimizes the percentage of errors that he can make during the treatment phase.